2020
DOI: 10.1534/g3.119.400612
|View full text |Cite
|
Sign up to set email alerts
|

Natural Genetic Variation Underlying Tiller Development in Barley (Hordeum vulgare L)

Abstract: In barley (Hordeum vulgare L.), lateral branches called tillers contribute to grain yield and define shoot architecture, but genetic control of tiller number and developmental rate are not well characterized. The primary objectives of this work were to examine relationships between tiller number and other agronomic and morphological traits and identify natural genetic variation associated with tiller number and rate, and related traits. We grew 768 lines from the USDA National Small Grain Collection in the fie… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 77 publications
(108 reference statements)
1
8
0
Order By: Relevance
“…These results suggest that genetic control of tillering at later developmental stages may at least in part be distinct from earlier stages. This idea is consistent with results from a recent genome-wide association study of tillering in a collection of 768 barley lines: tiller number at later time points was associated with more quantitative trait loci (QTLs) compared to early time points (Haaning et al 2020). Mutants M07.5478 and M08.0589 were especially interesting as they started tillering early resulting in higher numbers of fertile tillers.…”
Section: Discussionsupporting
confidence: 88%
“…These results suggest that genetic control of tillering at later developmental stages may at least in part be distinct from earlier stages. This idea is consistent with results from a recent genome-wide association study of tillering in a collection of 768 barley lines: tiller number at later time points was associated with more quantitative trait loci (QTLs) compared to early time points (Haaning et al 2020). Mutants M07.5478 and M08.0589 were especially interesting as they started tillering early resulting in higher numbers of fertile tillers.…”
Section: Discussionsupporting
confidence: 88%
“…However, in barley, little is known about the genetic mechanisms acting inside tiller buds to cause growth arrest. Although a quantitative trait locus (QTL) study revealed several genes associated with tiller number ( Haaning et al , 2020 ), the fact that some tillering genes do not overlap with identified QTLs point toward the complex involvement of environmental influence. Here, we show that the bHLH transcription factor gene INT-C is involved in the integration of different branching signals mediating a suppressive effect on bud outgrowth ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…As the association of tiller formation and yield or fertile tillers is also dependent on the developmental stage and environmental condition, only a modulation of INT-C function might be helpful. As INT-C was not detected among the genes in tiller QTLs ( Haaning et al , 2020 ), an easy association of the presence or absence of the gene with yield or fertile tillers is not possible.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The TN is controlled by multiple genes ( Haaning et al, 2020 ). At present, several candidate genes associated with TN have been reported in barley ( Bai et al, 2021 ), and several single genes that control TN have been identified in wheat ( Peng et al, 1998 ; Spielmeyer and Richards, 2004 ; Kuraparthy et al, 2007 ; Zhang et al, 2013 ; Wang et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%